2015
DOI: 10.1111/ijcp.12630
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of published studies of endothelial dysfunction does not support its routine clinical use

Abstract: Background: Endothelial dysfunction is a marker of future cardiovascular disease (CVD) risk, yet epidemiological studies have yielded inconsistent results. We therefore studied the association between endothelial dysfunction and CVD under diverse circumstances. Methods and results: Literature-based meta-analysis of prospective observational studies with ≥ 12 months of follow-up published in Medline and having information on endothelial function and CVD outcomes. Tabular data on participant characteristics, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…Findings from our meta-analysis may be influenced by participants in the studies testing fenofibrate [21][22][23]33,35,37,38]: they were obese and/or dyslipidemic and all had endothelial dysfunction at baseline (basal FMD < 6%, range 3.1-5%), representing a high-risk category, where improvement in the lipid profile is expected to exert beneficial effects on vascular health. Taking into account that low HDL-C and high triglycerides levels have been associated with reduced post-ischemic endothelial vasodilation, as shown in a cohort of patients with metabolic syndrome [58], findings of the present meta-analysis might contribute to the interpretation of results of FIELD and ACCORD trials [58,58,61].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Findings from our meta-analysis may be influenced by participants in the studies testing fenofibrate [21][22][23]33,35,37,38]: they were obese and/or dyslipidemic and all had endothelial dysfunction at baseline (basal FMD < 6%, range 3.1-5%), representing a high-risk category, where improvement in the lipid profile is expected to exert beneficial effects on vascular health. Taking into account that low HDL-C and high triglycerides levels have been associated with reduced post-ischemic endothelial vasodilation, as shown in a cohort of patients with metabolic syndrome [58], findings of the present meta-analysis might contribute to the interpretation of results of FIELD and ACCORD trials [58,58,61].…”
Section: Discussionmentioning
confidence: 74%
“…A recent Cochrane systematic review including 13 trials and 16,112 participants [4] demonstrates that fibrates exerts protective effects over the primary composite outcome (non-fatal stroke, non.fatal myocardial infarction and vascular death); however, after excluding clofibrate trials, the remaining class of fibrates were no longer effective in preventing the primary composite outcome but remained effective in preventing myocardial infarction. Furthermore, large-scale trials demonstrated that fenofibrate therapy reduces the rate of cardiovascular events only in patients at high risk, such as those with diabetes mellitus and atherogenic dyslipidemia (low levels of HDL-C and increased triglycerides) [58,58,61]. It is conceivable that trial results may considerably differ according to the background cardiovascular risk of participants.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies indicate that impaired flow-mediated dilation is a hallmark of various clinical conditions associated with increased cardiovascular risk; as for its prognostic capability, this seems to have been established in patients with relatively high cardiovascular risk profile. [11][12][13][14] All set, then? Well, not quite.…”
Section: See Article By Iantorno Et Almentioning
confidence: 99%
“…Well, not quite. For one thing, there is controversy over the prognostic role of endothelial function assessment in subjects at the lower end of cardiovascular risk profile, 13,14 in whom refining of classical indicators of cardiovascular risk would be most helpful. In addition, a major issue has to do with an overarching question: is endothelial function of peripheral arteries representative of what occurs at the coronary artery level?…”
Section: See Article By Iantorno Et Almentioning
confidence: 99%
See 1 more Smart Citation